The integration of Mobile Instant Messaging to a Peer-Interaction Programming Learning System (International Conference on Computers in Education, 2020)
Computer programming is essential knowledge in the digital age and becoming a critical subject during recent years. However, learn to program is not an easy topic, as supported by many researchers. During the development of information technology, many online learning systems have been developed and proven their positive effect on students learning. Many of them focused on helping students learn to program. However, few studies have geared toward supporting its use in programming courses with the support of instant messaging, which is extremely popular in the past few years. Therefore, this study aimed to upgrade an existed online learning system named PeerInteraction Programming Learning System to enhance students' peer-interaction by integrating with a mobile instant messaging service. In this paper, we reported on the development of the integration and its user interface, discussed our motivation and future work.